PENGARUH PRODUK, HARGA, DAN PROMOSI TERHADAP KEPUTUSAN KONSUMEN UNTUK MEMBELI BIG COLA DI SURABAYA - Ramadhani, Angga; Nasution, Ute Chairuz; Pratiwi, Ni Made Ida (Jurnal Dinamika Administrasi Bisnis, 2016)
Many Companies are trying to seize the market area in various ways in the show innovation in produdcts or services are produced. Companies must be able to determine appropriate market aspects so that the business can survive and the company’s main goal is reached. On the other hand many underlying factors that influence and consumers to buy such a product, the influence of product, price and promotion. Factors mentioned above become one of determining the consumer’s decision to buy a product. This study uses a quantitative method with multiple linear regression analysis. The purpose of this study to determine how much influence the product, price and promotion of consumer decision.Based on the research results, it can be seen that the product, price and promotion and very strong positive influence on consumer decision and variable promotion dominant influence over the decisions of consumer of the other variables. Keywords: Product, Price, Promotion, Consumer Decision.